A school for 'street children' (Journal of Parents and Teachers, 2026)
This institution, founded by the Jesuit Francisco Javier Fontova, is dedicated to providing both personal and educational support to children at social risk. It supports nearly 200 children through two programmes: the residential centre and the day centre. This project uses everyday life-based teaching methods and educational action plans to mitigate the effects of migration and promote social cohesion.
Keywords: Jesuit; Social risk; Holistic education; Inclusion